2014
DOI: 10.4149/gpb_2013056
|View full text |Cite
|
Sign up to set email alerts
|

Increased firing frequency of spontaneous action potentials in cerebellar Purkinje neurons of db/db mice results from altered auto-rhythmicity and diminished GABAergic tonic inhibition

Abstract: Abstract. The hormone leptin, by binding to hypothalamic receptors, suppresses food intake and decreases body adiposity. Leptin receptors are also widely expressed in extra-hypothalamic areas such as hippocampus, amygdala and cerebellum, where leptin modulates synaptic transmission. Here we show that a defective leptin receptor affects the electrophysiological properties of cerebellar Purkinje neurons (PNs). PNs from (db/db) mice recorded in cerebellar slices display a higher firing rate of spontaneous action … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…The decline in the amplitude and frequency of mEPSCs was in accordance with pre-and postsynaptic deficits, which corresponded with the loss of mushroom spines (the mature "memory spine") in the hippocampus of db/db mice. In contrast, the frequency of sEPSCs was increased, which may be due to the hyperexcitability of neurons in db/db mice 34 . Increased action potential (AP) frequency and decreased threshold potential of CA1 pyramidal neurons validated our assumption.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The decline in the amplitude and frequency of mEPSCs was in accordance with pre-and postsynaptic deficits, which corresponded with the loss of mushroom spines (the mature "memory spine") in the hippocampus of db/db mice. In contrast, the frequency of sEPSCs was increased, which may be due to the hyperexcitability of neurons in db/db mice 34 . Increased action potential (AP) frequency and decreased threshold potential of CA1 pyramidal neurons validated our assumption.…”
Section: Discussionmentioning
confidence: 88%
“…7d-f). Due to increased neuronal excitability in db/db mice 34 , we speculated that the elevation of sEPSCs may be associated with increased AP frequency. Our results demonstrated that the AP frequency increased and the threshold potential level slightly declined in the db/db mice, whereas the parameters recovered after Khk depletion (Fig.…”
Section: Loss Of Khk Rescues Aberrant Electrophysiology Of Ca1 Pyrami...mentioning
confidence: 99%
“…Specific nonrandom connectivity patterns in interneuronal networks connected by both GABAergic chemical and electrical synaptic contacts are essential for the function of the cerebellar cortical network [26]. Defective leptin receptors affect the electrophysiological properties of cerebellar PCs in a rodent model for obesity and type-2 diabetes [27]. Motor memories are postulated to be stored in the form of long-term depression/ potentiation not only at parallel fiber synapses with PCs, but also at several other synapses mostly dependent on calcium (reviewed in [28]).…”
Section: Introductionmentioning
confidence: 99%